RESEARCH OF THE LONG-TERM BEHAVIOUR OF THE PLEIADES BY USING OF PHOTOGRAPHIC PLATES FROM UKRVO DIGITAL ARCHIVE AND BALDONE OBSERVATORY - Kazantseva, L. V.; Andruk, V. M.; Shatokhina, S. V.; Protsyuk, Yu. I.; Eglitis, I.; Eglite, M. (Одеські астрономічні публікації, 2016)
The Pleiades Star Cluster (M45) is one of the most studied star clusters in the galaxy. At the same time as part of the Pleiades are many long-period variable stars, including flashing that need further study. Recent work on the processing of photographic images of the Pleiades obtained at different observatory revealed a number of star clusters with large variations in coordinates, the reason you want to understand. Collection of UkrVO unified digital archive contains a number of plates with images of the stars of the Pleiades obtained on different instruments. Processing of this material allows to test out standard programs for digital astronomical images processing. Also we will add information about variable stars and will improve the coordinates and proper motions of cluster stars. Selected material covers the period 1909 – 1999 years. The plates have different margins, scale, number of stars on images and obtained limiting magnitude. Exactly this diverse set of options lets you to be sure of results.